The End of the Progressive Narrative in Latin America (Alternautas, 2016)
Are we witnessing the end of the progressive governments’ cycle in Latin America? This question seems to come up after every electoral defeat or disappear whenever there is a victory. After more than a decade of continuous political successes in Venezuela, Argentina, Brazil, Uruguay, Ecuador, as well as other Central Americas countries, 2015 was the year that signaled adverse results and a drop in electoral support began. Without diminishing the importance of elections, whence the progressive governments derived their legitimacy, it is the time to evaluate the vitality of the political projects away from the narratives that constituted them in their peak moment. Beyond the polls, there looms an undetermined time of change. Due exhaustion of the model and to the internal transformation of the progressive, plurinational or Bolivarian political narrative (electoral defeats), we find a political language that was able to inscribe a new political time in Latin America, which comes to an halt with leaders involved in charges of corruption and as well as accompanied by the lowest indexes of popular support.